ANALISIS KINERJA PERAWAT DENGAN KEPUASAN PASIEN RAWAT INAP DI RSUD DOLOKSANGGUL KABUPATEN HUMBANG HASUNDUTAN - sartika, dewi (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2025)
To improve good health services as well as to increase patient satisfaction, hospitals need to implement one of the health service concepts that is difficult for many hospitals to implement in Indonesia, which has also been implemented by many developed countries to improve the quality of health services so that one of the health service quality indicators is achieved, namely by implementing Patient Centered care or what is also called PCC. The type of research was Quantitative Research using a Cross-Sectional approach. This research was carried out at Subulussalam City Regional Hospital. The research period started from December 2024 to March 2025. The population in this research was all Social Health Insurance Administration patients in the Subulussalam City Hospital Inpatient Room who were being treated at the time of the research with a total of 718 patient visits per month. The research respondents were 100 respondents. The sampling technique used was consecutive sampling. In consecutive sampling, all subjects who come and meet the selection criteria were included in the study until the required number of subjects is met. The results of the research shown that there is a statistical relationship between Health Services and Emotional Support (p = 0.04), Physical Comfort (p = 0.001), Information and education (p = 0.012), Service Coordination (p = 0.001) and Service Access (p = 0.003) in the Subulussalam City Hospital Inpatient Room in 2025. The Service Coordination variable is the most related to Health Services in the City Hospital Inpatient Room. Subulussalam seen from the Sig value. Service Coordination (0.001) and Service Coordination have a 4.471 chance of improving Health Services in the Subulussalam City Hospital Inpatient Room in 2025.